A rare complication after allogeneic stem cell transplantation: post‐transplant erythrocytosis. Issue 6 (2nd May 2016) - Atilla, Erden; Topcuoglu, Pervin; Ataca, Pinar; Pekcan, Gultekin; Bozdag, Sinem Civriz; Yuksel, Meltem Kurt; Ozcan, Muhit; Gurman, Gunhan; Toprak, Selami Kocak
Abstract: Post‐transplant erythrocytosis is an infrequent complication and has been reported after allogeneic hematopoietic stem cell transplantation (allo‐HSCT) in aplastic anemia, acute myeloid leukemia, and chronic myeloid leukemia. The pre‐disposing factors and treatment are not clearly defined. We present 11 post‐transplant erythrocytosis cases. More studies should be conducted to distinguish the pathogenesis and follow‐up for this rare complication.